Design of 28 GHz Microstrip Patch Antenna for Wireless Applications - Rana, Md Sohel; Moniruzzaman, Md.; Biswas, Anup Nirjhar; Azad, Tamanna; Mondal, Somapti; Islam, A.S.M. Tanvir Ul; Pal, Sourav; Islam, Rakibul; Islam, Md. Rabiul; Hossain, Sifat; Faruq, Omar; Shuva, Shubhra Kanti Sina (IAES Indonesian Section, 2023)
This research paper presents a 28 GHz microstrip patch antenna design and analysis for mobile phone applications. Fr-4 (lossy) material, whose dielectric permittivity is 4.3 and loss tangent is 0.025, has been used as a substrate material for the antenna. Besides, copper annealed has been used in the ground, and the thickness of the patch is 0.035. CST software creates and simulates the complete antenna. Among the results obtained from the simulation, return loss, VSWR, directivity gain, and bandwidth are -24.507 dB, 1.126, 7.19 dBi, and 1.352 GHz, respectively. The main objective of this proposed antenna is to achieve an excellent VSWR value by reducing the return loss, increasing the antenna's directivity gain, and improving the bandwidth. As a result, this proposed design can be used on super-high-frequency devices (mobile phones) in the future. The fact that the results obtained from the suggested antenna design are superior to those reported in papers published in the past hints that the research has achieved increased performance compared to studies already conducted in the field.